KINETIC STUDY OF THE SALT EFFECTS ON THE RATE OF REACTION BETWEEN MONOCHLORO ACETATE AND THIOSULPHATE IONS (Biological Sciences - PJSIR, 2002)
A bimolecular reaction was studied between monochloroacetate and sodium thi osulphate ions i n the presence of magnesium chloride. The temperature dependence of rate constant was eval uated at 40-70 °C. The val ues of activation energy (E) and activation parameter s such as chan ge i n enthalpy of activation (6 H ;t) , change i n entropy of activation (6 S ;t), and change in free energy of activation  (6 G ;o) were estimated  as a function of ionic  stren gth  (µ) of the mediu m .